2010
DOI: 10.1016/j.annepidem.2010.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Socioeconomic Status across Early Life on Age at Menarche Among a Racially Diverse Population of Girls

Abstract: Purpose-We evaluated the association between childhood socioeconomic status (SES) at two time points and age at menarche in a multiracial sample of U.S. girls.Methods-Our study population consisted of a cohort of female participants enrolled at birth in the New York site of the Collaborative Perinatal Project, born 1959Project, born -1963. SES at birth, at age 7, and change between birth and age 7 were measured prospectively through an index score of family income, paternal occupation, and education. Data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
88
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 34 publications
3
88
1
Order By: Relevance
“…-287-moderated by lower SES or inconsistent resources (e.g., Belsky et al, 2012;Deardorff et al, 2011;Ellis et al, 2009;James-Todd, Tehranifar, Rich-Edwards, Titievsky, and Terry, 2010;Simpson, Griskevicius, Kuo, Sung, and Collins, 2012). New experimental studies have even found that simply reminding women about paternal absence or disengagement (via priming) can alter their behavior (sexual thought/permissiveness, condom use) in ways consistent with psychosocial acceleration theory (DelPriore and Hill, 2013).…”
Section: Father Absence and Menarchementioning
confidence: 83%
“…-287-moderated by lower SES or inconsistent resources (e.g., Belsky et al, 2012;Deardorff et al, 2011;Ellis et al, 2009;James-Todd, Tehranifar, Rich-Edwards, Titievsky, and Terry, 2010;Simpson, Griskevicius, Kuo, Sung, and Collins, 2012). New experimental studies have even found that simply reminding women about paternal absence or disengagement (via priming) can alter their behavior (sexual thought/permissiveness, condom use) in ways consistent with psychosocial acceleration theory (DelPriore and Hill, 2013).…”
Section: Father Absence and Menarchementioning
confidence: 83%
“…Some studies have shown that lower SES is associated with earlier menarche, 20 while others have shown no association 21 or mixed results depending on the SES indicator examined. 722 One reason for equivocal findings may be that a variety of SES indicators are utilized across studies (e.g., family income, single parenthood, parental education, parental occupation, income-to-needs ratio and poverty), yet are referred to, collectively, as SES.…”
mentioning
confidence: 99%
“…For instance, using longitudinal data from the Collaborative Perinatal Project (n=262), James-Todd et al created an SES index (comprised of income, education, and occupation) and found that a 20-unit decrease in this index at age 7 was associated with a 4-month decrease in age at menarche later in life; however, specific indicators were not examined to assess unique SES effects. 20 Few studies have included multiple indicators concurrently to tease apart unique effects, and of those that have, there appear to be differential associations depending on the indicators used. Moreover, some evidence suggests that the timing of when SES indicators are measured (e.g., at birth versus later in childhood) may influence findings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To address this concern, analyses were adjusted for socioeconomic disadvantage (e.g., financial problems, maternal education) and maternal characteristics (maternal depression, maternal age at menarche) that have been linked to earlier menarche (Ellis and Garber 2000; James-Todd et al 2010) and are also associated with depression in adolescence (Gilman et al 2003; Petterson and Albers 2001). In addition, risk of parental breakdown is higher in families with lower levels of household income and educational attainment (Hankin et al 2010), higher levels of maternal depression (Agid et al 1999), and for those living in rented accommodation (Lupien et al 2009).…”
Section: Methodsmentioning
confidence: 99%